Pengaruh Variasi Mutu Beton Bertulang Terhadap Cepat Rambat Gelombang Dengan Menggunakan Metode Non Destructive Test - Lingga Ariya Dwisyahputra; Indradi Wijatmiko; Christin Remayanti Nainggolan (Rekayasa Sipil, 2020)
Preferably in testing, building structures need not be destroyed. Tests that can be used on the concrete can use non-destructive methods that do not damage the test objects. Examples of testing can use UPV tests that are aimed at knowing the quality of concrete from the pulse velocity. The test objects used in this study are reinforced concrete beams with dimensions 20 x 20 x 100 cm. Test objects are differentiated into 3 quality variations of reinforced concrete with quality of concrete12.5 MPa, 18.75 MPa, and 25 MPa. To conduct analysis of the concrete density used PUNDIT PL-200. Ultrasonic pulse velocity into parameters on this test. From the results of the tests, there are differences in the value of different coefficient of the R2 determination. Acquired coefficient value of determination R2 = 0.9076 in direct method. The coefficient value of determination R2 = 0.8718 in the semi-direct method. Coefficient value of determination R2 = 0.3042 at Indirect Method 2 point, and in indirect method 3 point the coefficient value of determination R2 = 0.7524. From this research also obtained comparisons between the three methods, namely between the direct method and the semi-direct method, direct method and indirect method, also semi-direct method and indirect method.